2000
DOI: 10.1103/physreva.61.053821
|View full text |Cite
|
Sign up to set email alerts
|

Intensity correlations in cavity QED

Abstract: The second-order intensity correlation function of light transmitted out of a cavity QED system exhibits the nonclassical features and dynamics of the atom-field interaction. We present measurements of the intensity correlation to examine the size of the nonclassical features and the dependence on driving intensity, detuning, and the strength of the atom-field coupling. We use a model that takes into account experimental conditions to achieve a quantitative agreement with the observations. PACS number͑s͒: 42.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(118 citation statements)
references
References 29 publications
4
114
0
Order By: Relevance
“…A number of optical studies, experimental and theoretical, have focused on the non-classical features as observed in the intensity correlations, eg. photon antibunching [13][14][15][16]. Our recent observations look, however, at the time dependence of the conditional fluctuations of the field [2] and its connection with the spectrum of squeezing.…”
Section: Introductionmentioning
confidence: 99%
“…A number of optical studies, experimental and theoretical, have focused on the non-classical features as observed in the intensity correlations, eg. photon antibunching [13][14][15][16]. Our recent observations look, however, at the time dependence of the conditional fluctuations of the field [2] and its connection with the spectrum of squeezing.…”
Section: Introductionmentioning
confidence: 99%
“…corresponding to the phenomenon of anti-bunching [10][11][12][13] which is associated with a single photon. …”
Section: Examplesmentioning
confidence: 99%
“…The coherence function g (2) (τ ) is a function of Ωτ = (τ /t)r, α, ξ, andn, where the preparation time t is the time that it takes the system to dynamically generate the Gaussian densityρ G given by (11) from the initial thermal stateρ 0 given by (9). Now…”
Section: Temporal Second-order Correlation Functionmentioning
confidence: 99%
“…Measurements of the normalized, second-order intensity correlation function for a stationary process of light emitted from a cavity QED system composed of N , two-level atoms coupled to a single mode of the electromagnetic field has been shown to exhibit the nonclassical features and dynamics of the atom-field interaction [9]. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%